The Development of Module Physics Learning Device Based on Inquiry Model by Concept Map Techniques in Improving Student Learning Outcomes - Rambe, Aslamiyah; Darwis, Muhammad; ., Abubakar; Abidan, Abdul Azis; Sahor Bangun Ritonga, Muhammad (KnE Social Sciences, 2023)
The development used in this research is 4-D model that consisted of defining, designing, development and dissimilating stage. In defining stage there were some process to be conducted, they were designing on learning device that covers syllabus, RPP, module, and LKS. On development stage the test of validity were done through validity sheet of learning device, practicality testing through observation sheet on the using RPP, questionnaire response of the teachers and the students, affectivity testing were obtained from the assessment of knowledge, attitude, characters, skills and the questionnaire of students response. Then, the disseminating of teaching device were done in disseminate stage. The result of the implementation of lesson plans, teacher’s response the questionnaires, student’s response questionnaires, it was found that the modules that had been developed were very valid with percentages 88,34%. The results of the implementation of RPP, teacher’s response questionnaires, student’s response questionnaires found that modules that have been developed are in the very practical category. Moreover, the cognitive assessment results 87,50%, psychomotor assessment 82,86 %, and affective assessment 80,17%. Thus, this research produces a physics learning model based on the map concept technique which can improve learning outcomes. Keywords: Physics learning; 4-D model; learning outcome; development